Adhesion analysis of single circulating tumor cells on a base layer of endothelial cells using open microfluidics. Issue 39 (23rd August 2018) - Mao, Sifeng; Zhang, Qiang; Li, Haifang; Zhang, Wanling; Huang, Qiushi; Khan, Mashooq; Lin, Jin-Ming
Abstract : We present a microfluidic method for adhesion strength analysis of single CTCs on endothelial cells to reveal tumor metastasis. Abstract : Circulating Tumor Cell (CTC) adhesion is essential in understanding the mechanism of metastasis. Although conventional methods for measuring adhesion strength have performed well on cell populations, a deeper insight into cell behavior demands new approaches for realizing non-destructive, high-resolution, in situ analysis of single cell adhesion. Here, we present a microfluidic method for adhesion strength analysis of single CTCs on a base layer of endothelial cells (ECs) to clarify cell-to-cell adhesion at single cell resolution. A confined flow in open space formed by a microfluidic device supplied a trypsin zone for the analysis of single cell adhesion. Tumor cell lines were used to model CTCs. This method was proved successful for extracting different types of CTCs from an endothelial cell layer to measure their adhesion strength by the time required for detachment. Moreover, we successfully uncovered the drug influence on the adhesion strength of single CTCs on ECs, which is promising in drug screening for tumor therapy. The current work reports a general strategy for cell-to-cell adhesion analysis for single cells.